Manganese in long term paediatric parenteral nutrition. Issue 6 (December 1994) - Reynolds, A P; Kiely, E; Meadows, N
Abstract : The current practice of providing manganese supplementation to neonates on long term parenteral nutrition is leading to a high incidence of hypermanganesaemia. Magnetic resonance imaging (MRI) studies in adults on long term manganese parenteral nutrition have shown changes in TI weighted MRI images and similar findings in a neonate receiving trace element supplementation are reported here. Whole blood manganese concentration in the infant was 1740 nmol/l (or 8.3 times upper reference limit). In all neonates on long term parenteral nutrition with evidence of cholestatic liver disease so far investigated, the whole blood manganese concentrations were > 360 nmol/l (reference range 73-210). Manganese supplementation to patients on long term parenteral nutrition requires reappraisal, particularly in those who develop cholestatic liver disease associated with parenteral nutrition.